Mediação de conceitos científicos e as barreiras linguísticas enfrentadas pelos intérpretes de Libras - Pinho, Graziela Cantelle de (2017)
The legal right to study in regular schools counting with the assistance of an Interpreter of Sign Language (ISL) was established in Brazil with the recognition of the Brazilian Language of Signals (BLS) by means of the Law 10.436 of the year 2002. When considering the use of BLS in inclusive science teaching, it is necessary to keep in mind that the BLS, being a young language in full development, still exhibits lack of vocabulary, mainly to express specific concepts. In classroom situations, the interpreter may have difficulties in adapting the technical language that expresses the technical-scientific content for BLS, being led to deal with situations that go beyond the interpretation of existing signs and to advance on a portfolio of signs related to their own experience of acting. Thus, the transmission of messages on specific subjects needs constant monitoring and evaluation. The general objective of this work is to investigate the mediation of scientific concepts in Portuguese Language for BLS using field data collection, with emphasis on the interpretation of scientific terms of the area of Physics, in particular, concepts on Electricity when mediated by the ISL acting in institutions of High and Higher Education in the western region of Paraná. For this, previously selected physics concepts were presented (orally, in Portuguese) to a group of ILS who performed the interpretation in BLS, which was filmed as a form of data recording. Subsequently these filming were presented to another group of ILS who watched the recordings and wrote in Portuguese what they understood from the interpretations recorded by the first ISL group. The video was also presented to two deaf teachers for a brief analysis. Finally, the messages were interpreted in relation to the original messages through direct confrontation. The analysis by confrontation indicates that the messages can be grouped in four classes, according to the fidelity to the content of the source message: (1) Message summarized with the replacement of words or expressions by equivalent terms; (2) Shortened messages omitting or deleting information; (3) Shortened messages by substituting words or expressions for non-equivalent terms; and (4) total mismatch between message source and target message. From the indirect analysis of the videos and from the testimonies of the deaf teachers about the filmed messages, we conclude that the process of interpretation does not always maintain the fidelity of content to the original message and the linguistic barriers in the interpretation process, such as lack of specific signs for technical and scientific terms and the lack of familiarity with the mediated subject can cause damages in the teaching and learning process of the deaf student.